1998
DOI: 10.1002/hep.510270331
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of assays for antibody to hepatitis E virus by a serum panel

Abstract: Few data are available to evaluate the performance of existing assays for antibody to the hepatitis E virus (anti-HEV). A panel of 164 randomized and coded sera was tested for anti-HEV by 12 different assays. The panel included a dilution series of an early convalescent human serum, known-positive sera (undiluted human sera obtained 2 months to 13 years after acute hepatitis E, and postinoculation chimpanzee sera), known-negative sera (preinoculation chimpanzee sera; sera from chimpanzees with hepatitis A viru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
163
0
2

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 208 publications
(174 citation statements)
references
References 31 publications
9
163
0
2
Order By: Relevance
“…This observation has been reported previously [18,19] and complicates the interpretation of cross-sectional HEV seroprevalence estimates based on results from a single assay. Preferentially, true seroprevalence estimates are adjusted for sensitivity and specificity of assays [24], but true sensitivity and specificity of assays are always unknown.…”
Section: Less Conservative Priormentioning
confidence: 65%
See 1 more Smart Citation
“…This observation has been reported previously [18,19] and complicates the interpretation of cross-sectional HEV seroprevalence estimates based on results from a single assay. Preferentially, true seroprevalence estimates are adjusted for sensitivity and specificity of assays [24], but true sensitivity and specificity of assays are always unknown.…”
Section: Less Conservative Priormentioning
confidence: 65%
“…Priors for sensitivity and specificity of each assay were based on the literature [19]. For assays based on similar antigens as E-2, sensitivity between 67 % and 91% was observed.…”
Section: Bayesian Analysismentioning
confidence: 99%
“…Until recently, commercial tests for anti-HEV IgG have demonstrated inconsistent sensitivity and specificity. The in-house NIH assay used in this study has higher sensitivity when compared with commercial assays Fix et al, 2000;Ghabrah et al, 1998;Mast et al, 1998). In fact, community-based surveys in 6000 subjects demonstrated that different lots of a commercial anti-HEV IgG ELISA varied considerably (for example, a second lot increased community-wide prevalence by 25% from 60-to-85%) (Fix et al, 2000).…”
Section: Introductionmentioning
confidence: 89%
“…21,22 The Walter Reed Army Institute of Research (WRAIR, Bethesda, MD) has developed a quantitative anti-HEV total Ig EIA that is highly sensitive (96%) and specific (98%) to identify HEV infections in populations. 23,24 The assay uses a quantitative sandwich approach to capture and label human Ig antibodies to recombinant HEV ORF2 proteins (rHEV) of the Sar-55 Pakistani strain expressed in the baculovirus system, and the photometric result is compared with positive controls from a reference pool of Nepali HEV patients, reporting antibody concentrations in WRAIR units per milliliter (WRAIR U/mL).…”
Section: Methodsmentioning
confidence: 99%